2010
DOI: 10.1007/s00134-010-2100-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double-blind, multicenter study comparing remifentanil with fentanyl in mechanically ventilated patients

Abstract: A prospective, randomized, double-blind, multicenter study comparing remifentanil with fentanyl in mechanically ventilated patients Abstract Purpose: To compare the quality of analgesia provided by a remifentanil-based analgesia regime with that provided by a fentanylbased regime in critically ill patients. Methods: This was a registered, prospective, two-center, randomized, triple-blind study involving adult medical and surgical patients requiring mechanical ventilation (MV) for more than 24 h. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
1
33
0
4
Order By: Relevance
“…A change from different combinations of flunitrazepam, midazolam, sufentanil and fentanyl to propofol and remifentanil was also associated with a shorter time to extubation [25]. In contrast to Rozendaal et al [26], Spies et al [27] reported no difference in weaning time.…”
Section: Discussionmentioning
confidence: 78%
“…A change from different combinations of flunitrazepam, midazolam, sufentanil and fentanyl to propofol and remifentanil was also associated with a shorter time to extubation [25]. In contrast to Rozendaal et al [26], Spies et al [27] reported no difference in weaning time.…”
Section: Discussionmentioning
confidence: 78%
“…Muellejans et al [17] compared remifentanil with fentanyl for analgesia and sedation of mechanically ventilated adult ICU patients and found quite similar extubation times of 1.1 h for remifentanil and 1.3 h for fentanyl. Spies et al [18] stopped their trial in mechanically ventilated adult patients ahead of time as a planned interim analysis could detect no advantage of remifentanil compared to fentanyl. The significant differences for remifentanil and fentanyl in our study demonstrate that neonates and young infants seem to benefit more than any other subgroup of patients from the unique pharmacokinetic properties of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…A recent mechanistic review suggests that remifentanil may be a cost effective sedative alternative when ICU length of stay is considered [91]. Superiority over fentanyl has not been demonstrated [92].…”
Section: Remifentanilmentioning
confidence: 99%